Simultaneous Bioremediation of Phenol and Cr (VI) from Tannery Wastewater Using Bacterial Consortium - Bhattacharya, Amrik; Gupta, Anshu; Kaur, Amarjeet; Malik, Darshan (International Journal of Applied Sciences and Biotechnology, 2015)
In the present study a consortium of four naturally isolated bacterial strains was evaluated as remediation tool for simultaneous removal ofphenol and Cr (VI) from tannery effluent. Application of bacterial consortia to effluent (pH 4.6) resulted in 100 and 78% removal of initial 47mg L-1 phenol and 16 mg L-1 Cr (VI), respectively at 96 h of treatment. The consortium was also active in removal of contaminants with lowerremoval rate in presence of extraneous higher concentrations of both phenol and Cr (VI). Treatment in static mode also resulted in removal ofpollutants, however with increase in agitation speed simultaneous reduction of contaminants becomes faster. Overall it can be inferred fromthe study that the above formulated bacterial consortium could effectively be used for treatment of phenol and Cr (VI) laden tannery and otherindustrial effluents. DOI: http://dx.doi.org/10.3126/ijasbt.v3i1.11889 Int J Appl Sci Biotechnol, Vol. 3(1): 50-55